Utility of a canine TSH assay for diagnosis and monitoring of feline hyperthyroidism - Urbanschitz, Tobias; Burgener, Iwan A.; Zeugswetter, Florian K. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2022)
Objective This retrospective study was initiated to evaluate the utility of TSH measurements using a common canine TSH assay to diagnose and monitor feline hyperthyroidism after radioiodine or thyreostatic drug treatment.Material and methods The electronic database of the University of Veterinary Medicine Vienna was searched for combined TSH and T4 measurements. 217 pairs of TSH and T4 from 136 cats with possible hyperthyroidism were assigned to group A (untreated; n = 24) and B (treated; n = 193). Measurements in group B were then subcategorized according to T4 concentrations (reference range 15–50 nmol/L): group B1 = elevated T4 (n = 46), group B2 = normal T4 (n = 84) and group B3 = decreased T4 (n = 63). Group B2 was further divided into cats with low normal (group B2a; n = 35), medium normal (group B2b; n = 29) and high normal (group B2c; n = 20) T4 concentrations.Results TSH was detectable in 4 (17 %) of the 24 untreated cats (group A) and did not return to normal despite seemingly successful therapy in two. Increased TSH concentrations were observed in 3.6 % of the treated cats in group B2 and 2.9 %, 6.9 %, and 0 % in subgroups B2a, B2b and B2c, respectively. Forty-four percent of the treated cats with a decreased T4 (group B3) had an increased TSH concentration. TSH correlated with treatment length (r = 0.358, p = 0.004) and was significantly higher in cats treated for more than 3 months (p = 0.008).Conclusion TSH was detectable in a significant number of untreated hyperthyroid cats and thus this parameter should not be used to definitively rule out feline hyperthyroidism. Furthermore, the very low prevalence of increased TSH concentrations in treated hyperthyroid cats with a normal T4 and cost benefit calculations do not support the routine measurement of TSH in these cats. The fact that TSH correlated with time since treatment start and 56 % of the cats with a decreased T4 had TSH concentrations within the reference limits, suggests delayed recovery of the pituitary thyrotrophs which might explain the low prevalence of subclinical hypothyroidism in the present study.Clinical relevance TSH measurement in cats with suspected or treated hyperthyroidism using a canine assay lacks diagnostic sensitivity and can only complement therapeutic decision-making.
Keywords: Cat; subclinical hypothyroidism; endocrinology; internal medicine